Flerstemmighed og bæredygtige rammer for kunstnerisk udvikling : interview med Miriam Frandsen og Dina Vester Feilberg fra Københavns nye kuraterede gæstespilsscene, Toaster - Gade, Solveig (Peripeti, 2022)
Multi-vocality and sustainable frameworks for artistic development: Interview with Miriam Frandsen and Dina Vester Feilberg from Toaster In 2021, Toaster was established as a new stage in Copenhagen for curated guest performances and for artistic practices in the cross field between theatre, performance and visual art. In the interview, Frandsen and Feilberg take stock of the project one year into it and share their reflections on how to work in a sustainable manner, both with regards to international collaborations, and to collaborations with self-producing companies working within a field marked by precarious working conditions.